Practicing Islam : Knowledge, Experience, and Social Navigation in Kyrgyzstan - Montgomery, David W., 1968- (Book collections on Project MUSE., 2016)
David W. Montgomery presents a rich ethnographic study on the practice and meaning of Islamic life in Kyrgyzstan. As he shows, becoming and being a Muslim are based on knowledge acquired from the surrounding environment, enabled through the practice of doing. Through these acts, Islam is imbued in both the individual and the community. To Montgomery, religious practice and lived experience combine to create an ideological space that is shaped by events, opportunities, and potentialities that form the context from which knowing emerges. This acquired knowledge further frames social navigation and political negotiation.Through his years of on-the-ground research, Montgomery assembles both an anthropology of knowledge and an anthropology of Islam, demonstrating how individuals make sense of and draw meanings from their environments. He reveals subtle individual interpretations of the religion and how people seek to define themselves and their lives as "good" within their communities and under Islam.Based on numerous in-depth interviews, bolstered by extensive survey and data collection, Montgomery offers the most thorough English-language study to date of Islam in post-Soviet Kyrgyzstan. His work provides a broad view into the cognitive processes of Central Asian populations that will serve students, researchers, and policymakers alike.